Conflict and fragmented public health emergency management system in Tigray region of Northern Ethiopia: A double burden to accommodate resilient and advanced public health emergency management. A commentary review for policy-makers and a call to action - Kiros Fenta Ajemu; Tsegay Hadgu; Gebremichael Gebreegziabher; Brhane Ayele; Hailay Gebretnsae; Abraham Aregay Desta; Hayelom Kahsay (BMC, 2024)
Abstract An estimated 2.5 million people have been internally and externally displaced in the Tigray region of northern Ethiopia in conflict and post-conflict settings. This induced a loss of access to basic and essential healthcare services. The situation was overwhelming, causing service inaccessibility, inadequate health facilities, unstable security to access the services, shortage of supplies and drugs, and medical equipment's in the region. The regional public health emergency management is one service delivery set up for the critically ill. It is characterized by weak emergency management capacities, poor coordination and integration. In addition, the system falls in to two independent sectors in the Tigray Health Bureau (THB), Tigray Health Research Institute (THRI). This leads to a fragmented system, an unclear leadership and governance role and a poor service delivery setup and tracking mechanism. The situation leads to resource duplication and poor business practice. Indeed, this type of service delivery setup secures personal and professional interest more than community interest. The situation exacerbated the occurrence of recurrent outbreaks in the region, with, for instance, zoonotic diseases (anthrax and rabies), acute watery diarrhoea, measles, malaria, yellow fever, and coronavirus disease 2019 (COVID-19) approaching to their level of epidemic. Moreover, they will spike as an epidemic in the future. All these circumstances made it evident that the system need reform to adhere with legal global, national, and regional frameworks, guidelines and proclamations. The system should have one service delivery set up at regional level. It must fall into regional public health institutes (PHIs) to adhere its service packages to the current advancements. Furthermore, integrated effort need from program implementers, relevant stakeholders and policy-makers should be committed and work together in the review and reform process.